Pengaruh Asal Anakan Terhadap Pertumbuhan Bibit Sagu Baruk - MALIANGKAY RONNY BERNHARD (Buletin Palma, 2010)
The Effect of Sucker Origin on Growth of Seedlings Arenga Microcarpa Propogation of sago baruk palms is vegetatif from sucker in stem internodes and sucker from roots. The good sucker for plant material has higher vigor. Therefore, the research was conducted to find of the effect of kinds sucker on the growth of sago baruk seeding. The experiment was conducted in the Kayuwatu experimental garden of Indonesian Research Institute for Coconut and other Palmae, Manado, North Sulawesi Province from August 2008 to Februari 2009, and it was arranged completed in a Randomized Design (CRD) with 8 replications, consisted of 2 kinds of sucker treatment. The treatments were (1) sucker from internodes stem with 4-5 leaves and (2) sucker from roots with 4-5 leaves. The results indication that sucker from internodes stem has higher vigor than sucker from roots.